Memory management in Hazelcast (International Journal of Engineering and Computer Science, 2024)
Hazelcast, an in-memory storage system, relies on efficient memory management to ensure seamless scalability and high-performance computing for distributed applications. Memory management in Hazelcast is a critical aspect that ensures optimal resource utilization, minimizes latency, and increases overall system reliability. This complex process involves allocating, releasing, and organizing memory resources according to the notes of the Hazelcast cluster. Understanding memory management in Hazelcast is important for developers and architects seeking to harness the full potential of this advanced in-memory data grid for their distributed applications.The purpose of the work is to consider Memory management in Hazelcast. To achieve this goal, the scientific works of domestic and foreign authors were used.